Improvement of physical and mechanical characteristics of gearbox shafts using the oxycarbonitriding method - Meshkov, Yu. Ye.; Dmitriev, M.S. (Problems of Tribology, 2025)
The article investigates the issue of promising methods for improving steels by modifying surface layers with the application of protective coatings. Priority areas of scientific research in the field of mechanical engineering have been identified for the development of new methods and technologies for increasing the wear resistance of steel surfaces by applying modified diffusion coatings. It has been shown that the key problem in optimizing the processes of saturation of metals and alloys with one element is cementation, nitriding, alitization, chromium plating, etc. Saturation with two or more elements is used very limitedly. The features of chemical-thermal treatment of steel are considered, with the help of which we have the opportunity to obtain a material characterized by increased characteristics and properties (surface hardness, corrosion resistance, wear resistance). Based on the identified features of coatings in terms of composition, structure, and properties, chemical-thermal treatment methods can be promising when operating them under wear conditions. However, the proposed innovative metallization method – oxy carbonitriding – can compete with these technologically complex processes. It was established that combined chemical-thermal treatment allows to increase the corrosion resistance of the material, the longer the oxycarbonitriding process time, the thicker the oxycarbonitrided layer.